2018
DOI: 10.1038/s41598-018-27217-3
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of hydroxysafflor yellow A against acute kidney injury via the TLR4/NF-κB signaling pathway

Abstract: This study aimed to evaluate the protective effect of hydroxysafflor yellow A (HSYA) on ischemia/reperfusion (I/R)-induced acute kidney injury via the TLR4/NF-κB pathway, both in vitro and in vivo. Rats were subjected to removal of the right kidney and I/R injury to the left kidney. Rats subjected to renal I/R injury were treated with HSYA at 0.5 h prior to I/R injury. Renal function, histopathological analysis, and cells apoptosis were measured in vivo. In vitro, proximal renal tubular cells (HK-2) were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 40 publications
5
41
0
Order By: Relevance
“…TLR‐4 leads to phosphorylation of the transcription factor NF‐κB, which induces proinflammatory cytokine production as TNF‐ α that leads further liver damage (Mahmoud et al, ). In contrast, the anti‐inflammatory factor IL‐10 was suppressed (Gendy et al, ; Bai et al, ). This well explains our findings where IR resulted in increased gene expression of both NF‐κB‐p65 and TLR‐4 consequently increased TNF‐ α and INF‐γ.…”
Section: Discussionmentioning
confidence: 99%
“…TLR‐4 leads to phosphorylation of the transcription factor NF‐κB, which induces proinflammatory cytokine production as TNF‐ α that leads further liver damage (Mahmoud et al, ). In contrast, the anti‐inflammatory factor IL‐10 was suppressed (Gendy et al, ; Bai et al, ). This well explains our findings where IR resulted in increased gene expression of both NF‐κB‐p65 and TLR‐4 consequently increased TNF‐ α and INF‐γ.…”
Section: Discussionmentioning
confidence: 99%
“…They found HSYA prevented I/R induced apoptosis in kidney epithelial cells in vivo and in vitro. HSYA may attenuate TLR4 signaling to prevent apoptosis in kidney epithelial cells (Bai et al, 2018). Increasing the stability of HSYA in XBJ may further enhance the protection to the kidney (Pu et al, 2017).…”
Section: C0127 Prevents C Albicans-induced Kidney Failurementioning
confidence: 99%
“…It is also reported that hydroxysafflor yellow A protected against acute kidney ischemia/reperfusion injury via the TLR4/NF-κB signaling pathway. 52 However, the role of TLR4/NF-κB signaling pathway in flap IR injury has not been reported yet. The results showed that the expression levels of TLR4 and galectin-3 were significantly increased after IR, and such outcomes were partially reversed by rhGH treatment.…”
Section: Tlr4 and P65 Participated In The Development Of Ir Flapmentioning
confidence: 99%